On grand strategy - Gaddis, John Lewis (New York : Penguin Press, 2018)
Distilled from the Yale University seminar, "Studies in Grand Strategy," a master class in strategic thinking surveys statecraft from the ancient Greeks through FDR and beyond as vital historical lessons for future world leaders.
"John Lewis Gaddis, the distinguished historian of the Cold War, has for almost two decades co-taught grand strategy at Yale University with his colleagues Charles Hill and Paul Kennedy. Now, in [this book], Gaddis reflects on what he has learned. In chapters extending from the ancient world through World War II, Gaddis assesses grand strategic theory and practice in Herodotus, Thucydides, Sun Tzu, Octavian/Augustus, Saint Augustine, Machiavelli, Elizabeth I, Philip II, the American Founding Fathers, Clausewitz, Tolstoy, Lincoln, Wilson, Franklin D. Roosevelt, and Isaiah Berlin. On Grand Strategy applies the sharp insights and wit readers have come to expect from Gaddis to times, places, and people he's never written about before. For anyone interested in the art of leadership, On Grand Strategy is, in every way, a master class."--Dust jacket.
Crossing the Hellespont -- Long walls -- Teachers and tethers -- Souls and states -- Princes as pivots -- New worlds -- The grandest strategists -- The greatest president -- Last best hope -- Isaiah.
Includes bibliographical references and index.
Keywords: Strategy; Strategy -- History; Military art and science; Strategic culture; Military art and science; HISTORY / Military / Other; TECHNOLOGY & ENGINEERING / Military Science; Nonfiction